Reading the Taring Padi Cardboard Puppet Workshop in the Documenta Fifteen for the 2021-2022 Period Through the Perspective of Pablo Helguera - Rio Aji Nusantara Putra S.; Muhammad Kholid Arif R; Rr Vegasari Adya Ratna (TUMATA: Journal of Arts and Cultural Management, 2025)
Participatory art has grown significantly as a response to the sense of alienation experienced by society within contemporary art practices. In Indonesia, this phenomenon emerges in various forms, one of which is the Wayang Kardus workshop initiated by the art collective Taring Padi. This research aims to analyze the management of the Wayang Kardus workshop through the perspective of participatory art as developed by Pablo Helguera (socially engaged art). A qualitative descriptive approach is employed to explore the dynamics of the workshop’s management, focusing on Helguera’s six principles: collaboration, transpedagogy, performativity, documentation, deskilling, and social situations. Data were collected through in-depth interviews and documentation studies. The findings indicate that Taring Padi’s management practices reflect all six of Helguera’s principles within the Indonesian local context. Collaboration is manifested through collective work and equitable role distribution; transpedagogy is evident in the reciprocal learning process between facilitators and participants; performativity is realized through creative actions in public spaces; documentation functions as a form of critical archive; deskilling enables the inclusion of non-artist participants; and social situations encourage art practices that are contextually grounded and relevant to community conditions. In conclusion, the management of Taring Padi’s Wayang Kardus workshop represents an art practice rooted in social engagement, emphasizing equitable power distribution, sensitivity to community contexts, and the sustainability of relationships between artists and participants.